Neotipificacion de Hechtia lanata (Bromeliaceae, Hechtioideae), especie endemica de Oaxaca, Mexico - Espejo Serna, A.=700 1 Lopez Ferrari, A.R.; Ceja Romero, J.; Mendoza Ruiz, A.
(Es, En)
Ilus., 13 ref.
Keywords: BROMELIACEAE; TAXONOMIA; DISTRIBUCION GEOGRAFICA; HABITAT; MEXICO; HECHTIA LANATA